The AusAB non-ribosomal peptide synthetase of Staphylococcus aureus preferentially generates phevalin in host-mimicking media - Adriana Moldovan; Markus Krischke; Claudia Huber; Clara Hans; Martin J. Müller; Wolfgang Eisenreich; Thomas Rudel; Martin J. Fraunholz (mBio)
ABSTRACT Non-ribosomal peptide synthetases (NRPSs) are modular multidomain enzymes responsible for the biosynthesis of various secondary metabolites in an mRNA template-independent manner. They are predominantly present in bacteria and fungi, where they synthesize a variety of products, including antibiotics, siderophores, toxins, and signaling molecules. The human pathogen Staphylococcus aureus possesses one single NRPS, AusA, highly conserved in all sequenced S. aureus strains. AusA incorporates the aromatic amino acids (AAAs) phenylalanine or tyrosine, as well as the branched-chain amino acids valine and leucine into three cyclic dipeptides collectively called aureusimines: phevalin, tyrvalin, and leuvalin. By using targeted metabolomics, we found that during growth in the common tissue culture medium RPMI1640, AusA preferentially synthesizes phevalin, despite similar availability for both phenylalanine and tyrosine. Upon cultivation in a chemically defined medium, however, the yields for both products are comparable, albeit with a slight preference for phevalin. Moreover, omission of either “building block” (phenylalanine, tyrosine, or valine) does not abrogate aureusimine biosynthesis, showing that de novo biosynthesis of these amino acids is sufficient to yield aureusimine production. Cultivation of S. aureus in a synthetic medium mimicking human nasal secretions, lacking tyrosine, results in marked phevalin production, despite moderate bacterial growth. Our report on culture medium composition-driven AAA incorporation by a bacterial NRPS provides a useful basis for linking bacterial cell metabolic status to the biosynthesis of secondary metabolites.IMPORTANCEPeptide and protein synthesis are fundamental processes in nature which are largely mediated by the ribosomal machinery. An alternative pathway for peptide synthesis is non-ribosomal mRNA template-independent synthesis, performed by so-called NRPSs. NRPSs are multi-enzyme complexes which serve the simultaneous role of template and biosynthetic machinery. They are mostly found in bacteria and fungi and are responsible for the biosynthesis of many pharmacologically significant products, including antibiotics, anticancer compounds, or immunosuppressants. The human pathogen S. aureus possesses one such NRPS, AusA, which synthesizes three cyclic dipeptides termed “aureusimines” using the aromatic amino acids phenylalanine and tyrosine and the branched-chain amino acids leucine and valine. Although the biological role of aureusimines remains unknown, AusA appears to play a role in the interaction of S. aureus with the host. In addition, owing to its minimal canonical NRPS structure and autonomous function (i.e., most NRPS pathways require the assembly of several NRPS proteins), AusA represents an excellent model system for studying such molecular assembly lines. Our observation is, to our knowledge, the first report of an NRPS showing preferential incorporation of aromatic amino acids, despite their similar availability.